Do the COVID-19 Crisis, Ageing and Climate Change Put Swiss Fiscal Sustainability at Risk? - Thomas Brändle; Pierre-Alain Bruchez; Carsten Colombier; Martin Baur; Lukas Hohl (Intereconomics)
Abstract The ongoing coronavirus pandemic crisis as well as demographic and climate change pose major challenges for public finances. This article deals with the implications of demographic trends in Switzerland, i.e. the progressive ageing of the population and its impact on the country’s public finances in the long run. As the analysis shows, the brunt of the demographic burden is borne by the old-age pension scheme, health and long-term care. This article also addresses the financial ramifications of the COVID-19 crisis and shows the need for economic policy action over the longer term to ensure the sustainability of public finances in Switzerland. Furthermore, a qualitative assessment of climate change is included, as it constitutes an additional major long-term challenge for public finances.